Legal Protection in the Fair Implementation of Mortgage Rights - Frida Nurrahma Masturi; Normalita Destyarini; Asep Herlan (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2026)
This research aims to analyze the application of the principles of balance and good faith in the enforcement of mortgage rights, with a particular focus on ensuring proportional legal protection for debtors. Although the Mortgage Law provides legal certainty for creditors, execution practices frequently disadvantage debtors, especially regarding auction pricing, notification mechanisms, and creditor conduct in determining default. Using a normative juridical method with statutory and conceptual approaches, this study finds that debtor protection should not merely rely on formal declarations of default, but must also consider factual conditions, including force majeure circumstances and the debtor’s good faith. The implementation of procedural transparency, objective pre-execution mechanisms, and the principle of balance is essential to prevent abuse of rights by creditors and to ensure that execution serves as a last resort. Therefore, harmonizing legal certainty, justice, and utility is indispensable to create a fair legal relationship between creditors and debtors in the execution of mortgage rights.